Wearable Biodevices Based on Two-Dimensional Materials: From Flexible Sensors to Smart Integrated Systems - Sun, Yingzhi; He, Weiyi; Jiang, Can; Li, Jing; Liu, Jianli; Liu, Mingjie (Nano-Micro Letters, 2025)
The proliferation of wearable biodevices has boosted the development of soft, innovative, and multifunctional materials for human health monitoring. The integration of wearable sensors with intelligent systems is an overwhelming tendency, providing powerful tools for remote health monitoring and personal health management. Among many candidates, two-dimensional (2D) materials stand out due to several exotic mechanical, electrical, optical, and chemical properties that can be efficiently integrated into atomic-thin films. While previous reviews on 2D materials for biodevices primarily focus on conventional configurations and materials like graphene, the rapid development of new 2D materials with exotic properties has opened up novel applications, particularly in smart interaction and integrated functionalities. This review aims to consolidate recent progress, highlight the unique advantages of 2D materials, and guide future research by discussing existing challenges and opportunities in applying 2D materials for smart wearable biodevices. We begin with an in-depth analysis of the advantages, sensing mechanisms, and potential applications of 2D materials in wearable biodevice fabrication. Following this, we systematically discuss state-of-the-art biodevices based on 2D materials for monitoring various physiological signals within the human body. Special attention is given to showcasing the integration of multi-functionality in 2D smart devices, mainly including self-power supply, integrated diagnosis/treatment, and human–machine interaction. Finally, the review concludes with a concise summary of existing challenges and prospective solutions concerning the utilization of 2D materials for advanced biodevices. Highlights: 1 Two-dimensional (2D) materials are highlighted for their exceptional mechanical, electrical, optical, and chemical properties, making them ideal for fabricating high-performance wearable biodevices. 2 The review categorizes cutting-edge wearable biodevices by their interactions with physical, electrophysiological, and biochemical signals, showcasing how 2D materials enhance these devices’ functionality, mainly including self-powering and human-machine interaction. 3 2D materials enable multifunctional, high-performance biodevices, integrating self-powered systems, treatment platforms, and human-machine interactions, though challenges remain in practical applications.